Demographic Change and Governance Issues (The Pakistan Development Review, 2006)
Pakistan is the 6th most populous country in the world while it ranks 4th in Asia. Its population has increased from 34 million in 1951 to an estimated 160 million in the year 2006, growing at the rate of three million persons per year. At this speed of growth, Pakistan’s population is projected to reach the 220 million mark by the year 2020; as we arrive at the Population Replacement Level. While Population Growth Rate (PGR) has declined from over 3 percent in previous decades to its current level of 2.1 percent per annum, which is, nevertheless, the highest population growth rate in South Asia, a dubious achievement when compared to the situation in the neighbouring countries. Therefore, the government policy remains intact, which is to lower population growth rate from its current level to 1.3 percent per annum by the year 2020, to reduce the total fertility rate to 2.1 percent and to reach replacement level of fertility by the year 2020. Unless its growth rate swiftly, by the year 2060, Pakistan is destined to become the 4th most populated country in the world, its population reaching over 305 million mark. In 1950s it was ranked 14.